MCM-41-supported platinum carbonyl cluster-derived asymmetric hydrogenation catalyst - Basu, Susmit; Paul, Himadri; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Catalysis, 2005)
Anionic platinum carbonyl cluster has been ion paired with cinchonidium groups that are chemically bound to the surface of MCM-41 and fumed silica. In the hydrogenation of methyl pyruvate or acetophenone the fumed silica-based catalyst gives zero enantioselectivity, but under optimum conditions enantiomeric excesses of >90 and similar to40%, respectively, are obtained with the MCM-41-based catalyst. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: asymmetric catalysis; functionalized inorganic oxides; hydrogenation catalysts; platinum carbonyl cluster

MCM-41-supported platinum carbonyl cluster-derived catalysts for asymmetric and nonasymmetric hydrogenation reactions - Basu, Susmit; Mapa, Maitri; Gopinath, Chinnakonda S.; Doble, Mukesh; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Catalysis, 2006)
Anionic platinum carbonyl Cluster ([Pt-12(CO)(24)](2-)) was ion-paired with the 3-chloropropyltrimethoxysilyl-ammonium group chemically bound to the surface of MCM-41. The materials undergo quick decarbonylation and have been characterized before decarbonylation by IR and UV-vis spectroscopy and after decarbonylation by XPS and TEM. They have been used as catalysts for the hydrogenations of methyl pyruvate, acetophenone, nitrobenzene, benzonitrile, and ethylacetoacetate. The support and the quaternary ammonium groups have significant effects on surface platinum concentration, crystallite size, and observed activity. In the hydrogenation of the prochiral substrates methyl pyruvate or acetophenone, the cinchonidine-based catalyst gives significant enantioselectivity under optimum conditions. A kinetic model that includes an enantioselective product-formation step and a hydrogen pressure-dependent step for the deactivation of the enantioselective sites gives reasonable agreement between predicted and observed enantioselectivity. The model is also in accordance with the XPS and TEM data. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: asymmetric/non-asymmetric catalysis; Enantioselectivity; functionalized MCM-41; hydrogenation catalysts; platinum carbonyl cluster

Metal-induced reductive ring opening of 1,2,4,5-tetrazines: Three resulting coordination alternatives, including the new non-innocent 1,2-diiminohydrazido(2-) bridging ligand system - Maji, Somnath; Sarkar, B.; Patra, S.; Fiedler, Jan; Mobin, Shaikh M.; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Inorganic Chemistry, 2006)
{Reaction of 3,6-diaryl-1,2,4,5-tetrazines (aryl = R = phenyl, 2-furyl or 2-thienyl) with 2 equiv of Ru(acac)(2)(CH3-CN)(2) results in reductive tetrazine ring opening to yield diruthenium complexes [
Keywords: crystal engineering; hydrogen bonds; molecular; recocynition; Self-assembly; supramolecular chemistry

MCM-41-supported organometallic-derived nanopalladium as a selective hydrogenation catalyst - Maity, Niladri; Rajamohanan, Pattuparambil R.; Ganapathy, Subramanian; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Physical Chemistry C, 2008)
Palladium nanocatalysts have been prepared by anchoring (eta(3)-C(3)H(5))(2)Pd(2)Cl(2) onto dian-tine-functionalized MCM-41 supports followed by reaction with hydrogen under catalytic conditions. The catalyst precursor and used catalyst have been studied by solid-state NMR ((13)C, (29)Si), XPS, and TEM. The organometallic-derived catalyst exhibits the best performance (activity and selectivity) to date toward the selective hydrogenation of industrially relevant o- and m-chloronitrobenzene to the corresponding chloroaniline derivatives and is distinctly superior to 5% Pd/C. Grazing angle XPS studies reveal that conversion of the tethered molecular species to the nanoparticles of palladium produces a core-shell nanostructure.

MCM-41-supported ruthenium carbonyl cluster-derived catalysts for asymmetric hydrogenation reactions - Indra, Arindam; Basu, Susmit; Kulkarni, Dhanashree G.; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Applied Catalysis A-General, 2008)
{The anionic ruthenium carbonyl cluster [Ru-4(mu-H)(3)(CO)(12)](-) has been ion-paired with (3-chloropropyl)-trimethoxysilyl-cinchonidium or sparteinium groups chemically bound to the surfaces of MCM-41 [(MCM-41-)(-O)(3)SiCH2CH2CH2NR3+Cl-
Keywords: asymmetric catalysis; functionalized MCM-41; hydrogenation catalysts; nanocatalyst; ruthenium carbonyl cluster